Evaluation of BACTEC system for urine culture screening. - Colombrita, D (1989)
We compared urine culturing performed by the calibrated loop method with a screening system (BACTEC). A total of 852 urine specimens were examined by both the conventional loop method and the BACTEC system. With the loop method, 193 (22.6%) urine samples were positive, whereas with the BACTEC system, 185 (21.7%) were positive (sensitivity, 96.01%). At a breakpoint of 10(4) CFU/ml, eight false-negatives were detected (sensitivity, 87.09%), and at a breakpoint of 10(5) CFU/ml, four false-negatives were observed (sensitivity, 97.6%). The specificity of the BACTEC system was 100%. We propose the BACTEC method as an effective alternative to the other growth-dependent screening tests for bacteriuria.